Energy consumption, CO2 emissions, and economic growth: An ethical dilemma. (February 2017) - Antonakakis, Nikolaos; Chatziantoniou, Ioannis; Filis, George
Abstract: In this study we examine the dynamic interrelationship in the output–energy–environment nexus by applying panel vector autoregression (PVAR) and impulse response function analyses to data on energy consumption (and its subcomponents), carbon dioxide emissions and real GDP in 106 countries classified by different income groups over the period 1971–2011. Our results reveal that the effects of the various types of energy consumption on economic growth and emissions are heterogeneous on the various groups of countries. Moreover, causality between total economic growth and energy consumption is bidirectional, thus making a case for the feedback hypothesis. However, we cannot report any statistically significant evidence that renewable energy consumption, in particular, is conducive to economic growth, a fact that weakens the argument that renewable energy consumption is able to promote growth in a more efficient and environmentally sustainable way. Finally, in analysing the case for an inverted U-shaped EKC, we find that the continued process of growth aggravates the greenhouse gas emissions phenomenon. In this regard, we cannot provide any evidence that developed countries may actually grow-out of environmental pollution. In the light of these findings, the efficacy of recent government policies in various countries to promote renewable energy consumption as a means for sustainable growth is questioned. Put differently, there seems to be an ethical dilemma, between high economic growth rates and unsustainable environment and low or zero economic growth and environmental sustainability.